2016
DOI: 10.21608/pssjn.2016.32525
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Performance Regarding Caring of Patients Undergoing Blood Transfusion

Abstract: Background: Blood transfusion is an essential component of modern health care that saves millions of lives each year, and it will continue to be so for many years to come.Aim : the current study aimed to assess nurses' performance regarding nursing care of patients undergoing blood transfusion. Subjects and Methods : A descriptive research design was utilized in this study. The study was carried out at three hospitals affiliated to the Ministry of Health (Port-Said General Hospital, Port -Fouad General Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Regarding the relationship between nursing knowledge and practice, Hendy et al, (34) discovered a positive correlation between the overall level of nurses' knowledge and their practice (r<0.65). In addition, Saied et al, (35) discovered that nurses' total knowledge and total practice scores were positively correlated. Our results showed that highly statistically significant deference between total practice and total factors (P <0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the relationship between nursing knowledge and practice, Hendy et al, (34) discovered a positive correlation between the overall level of nurses' knowledge and their practice (r<0.65). In addition, Saied et al, (35) discovered that nurses' total knowledge and total practice scores were positively correlated. Our results showed that highly statistically significant deference between total practice and total factors (P <0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of this examine had been consisted of all nurses (150) who had been operating with inside the above referred to placing of in depth care devices (ICU) and offer direct take care of sufferers present process blood trans-fusion allotted as the subsequent: (50) nurses in Anaesthesia Intensive Care Units, (35) nurses in in depth care devices in Medical Hospital, (35) nurses in cardiac and (30) nurses in neurological in depth care devices affiliated to Tanta University Hospital. .…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The community must get high-quality medical care through hospitals, which serve as the primary organization for the delivery of public services. In accordance with these provisions, there are four sections pertaining to hospitals' obligations in providing medical services, namely: Responsibility for employees: competent personnel must be hired through an open and transparent hiring process, professional Thalassemia Syndromes -New Insights and Transfusion Modalities responsibility for quality: Professional bodies are always required to set up ongoing training programs for their members in blood transfusion services in order to comply with international best practices, responsibility for facilities and equipment; appropriate financing should be available to supply the tools and supplies that medical professionals, particularly those working in blood transfusion units, need; and Last but not least, the hospital is responsible for the building's safety and upkeep [32][33][34]. This includes making sure that both patients and staff are safe inside the institution.…”
Section: Establishing Multicenter Cooperative Transfusion Servicementioning
confidence: 99%
“…Healthcare facilities in Nigeria should make every attempt to keep everyone's values and presumptions in mind as it may affect interactions with team members who are other professionals. Regardless of the talents and limitations of various team members, effective teamwork contributes to the provision of high-caliber and safe healthcare [33,34]. Hospitals must create a blood transfusion committee that meets regularly to examine the current transfusion strategy, and best practices, compile a transfusion manual and handbook, as well as to take training sessions to stay informed about the current state of transfusion services [34].…”
Section: Establishing Multicenter Cooperative Transfusion Servicementioning
confidence: 99%